PENGARUH BRANDIMAGE, KUALITASPRODUK, DANHARGA TERHADAPKEPUTUSANPEMBELIANDICHATIME TRANSMART RUNGKUT SURABAYA - Muarifah, Indah; Mulyati, Awin; Andayani, Sri (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACT Chatime is one of beverage products are drinks made from tea byaddinga special ingredient, which is bubble. Thewell-known brand image, good product quality and competitive prices make Chatime beverage products rankedfirstin Bubble Drink sales.This study aims to determine and analyze the effect of Brand Image, Product Quality and Price on the Purchase Decision of Chatime beverage products in Transmart Rungkut Surabaya. The population of this researchis all consumers of Chatime from Surabaya. Samples were taken as many as 100 people based on purposive sampling method. There sults showed that Brand Image and Price hada positive and significant effecton Purchasing Decisions. While the Product Quality does not significantly influence Purchasing Decisions. Because of the product quality is recognized as good so it does not affect the purchase decision.This study also explained that the Purchasing Decision influenced the model by25.8% while there maining 74.2% was influenced by variables or other factors not examined inthisstudy. For example the promotion variable, service quality, location, franschise atmosphere, product quality, product variation and other variables. Keywords:Brand Image, Product Quality, Price,Purchase Decision